Serum uric acid to serum creatinine ratio predicts neurological deterioration in branch atheromatous disease - Liu, Yinglin; Wang, Honglei; Xu, Ronghua; He, Lanying; Wu, Kun; Xu, Yao; Wang, Jian; Xu, Fan (Frontiers in Neurology, 2023)
Background and objective Branch atheromatous disease (BAD) makes patients prone to early neurological deterioration (END), resulting in poor prognosis. The aim of this study was to investigate the association between SUA/SCr and END in BAD stroke patients. Methods We conducted a retrospective study that included 241 patients with BAD-stroke within 48 h of symptom onset. We divided the patients into the END group and the no END group. END was defined as an NIHSS score increase of more than 2 points within 1 week. SUA/SCr was calculated by the concentration of serum uric acid and creatine (serum uric acid/serum creatine) on admission. Univariate and multivariate analyses were used to identify independent predictors of END in BAD-stroke patients. Results END was observed in 24.1% (58/241) of the patients in our study. Multiple logistic regression analyses showed that SUA/SCr (aOR, 0.716; 95% CI, 0.538–0.952; P = 0.022) and female sex (aOR, 0.469; 95% CI, 0.245–0.898; P = 0.022) were associated with END after adjusting for confounding factors. The predicted value of SUA/Scr for END was a sensitivity of 79.3%, a specificity of 44.8%, and an AUC of 0.609 (95% CI, 0.527–0.691, P < 0.05). The optimal cut-off value was 4.76. Conclusion SUA/SCr was negatively associated with the risk of END in BAD stroke patients.